Sn-119 magic angle spinning NMR of nanocrystalline SnO2 - Sabarinathan, V.; Chandran, C. Vinod; Ramasamy, S.; Ganapathy, Subramanian (Journal of Nanoscience and Nanotechnology, 2008)
Nanocrystalline SnO2 samples of different grain sizes, prepared by inert gas condensation technique (IGCT) and chemical precipitation method and conforming to the tetragonal phase, have been studied by variable speed (3-10 kHz) Sn-119 MAS NMR at 11.74 Tesla field. Sn-119 solid-state NMR results show that the IGCT prepared samples have good crystallinity and phase purity compared to the samples prepared by the chemical method. The determination of Sn-119 chemical shielding parameters (delta(iso), Delta delta and eta) from slow MAS spectra shows that the Sn-119 isotropic chemical shift (delta(iso)) is strongly influenced at smaller grain sizes, attributable to the change in the O2- local symmetry for the surface Sn-119 ions at smaller grain sizes. The observed line widths in MAS spectra are significantly larger than the life-time broadening due to spin-lattice (T-1) and spin-spin (T,) relaxation. The Sn-119 MAS NMR spectra are thus inhomogeneously broadened by a distribution of isotropic chemical shifts, the line broadening increasing with decrease in grain size.
Keywords: Hydrolysis; IGCT; MAS NMR; nanocrystalline SnO2

Sensitivity enhancement of Si-29 double-quantum dipolar recoupling spectroscopy by Carr-Purcell-Meiboom-Gill acquisition method - Goswami, M.; Madhu, Perunthiruthy K.; Dittmer, J.; Nielsen, N. C.; Ganapathy, Subramanian (Chemical Physics Letters, 2009)
An enhancement in the detection sensitivity of dipolar recoupled Si-29 double-quantum magic-angle spinning experiment is shown with a Carr-Purcell-Meiboom-Gill (CPMG) train of pi pulses during the acquisition period. Symmetry-adapted pulse schemes, such as POST-C7 and SR26(4)(11), are used for the double-quantum excitation. Application of POST-C7-CPMG method for framework characterisation is demonstrated in the disordered and catalytically important ZSM-5 molecular sieve. Based on the observed double-quantum dipole-dipole correlations and the known T-site Si connectivities, the assignment of all the signals is made for the orthorhombic phase of the as-synthesised (CN form) material. (C) 2009 Elsevier B. V. All rights reserved.